The Utilization of Database for Administration Purposes as a Strategy Facing the New Normal: Prototype Development of e-Office - Mustofa, Fahmi Charish; Ahmad, Umar Ali; Nugroho, Bangkit Indarmawan (Sekolah Tinggi Pertanahan Nasional, 2023)
The rise of Industry 4.0 has revolutionized work dynamics, particularly evident in the widespread adoption of remote working practices. Employees are no longer confined to traditional office spaces; instead, they have the flexibility to work efficiently from various locations. This study delves into the creation of a remote presence application, named